2003
DOI: 10.1007/s00068-003-1332-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of Individual Three-Dimensional Bone Substitutes Using “Selective Laser Melting”

Abstract: Aim and Background: Scientific approach is the utilization of the new generative manufacturing process termed Selective Laser Melting (SLM) for the creation of biocompatible three-dimensional (3-D) bone substitutes made of the titanium alloy TiAl6V4. The SLM technique enables direct transfer of virtual 3-D structures into solid metal materials with full serial characteristics and typically great freedom of geometric design. Material and Methods: Individual 3-D CAD data which are derived from computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 17 publications
(24 reference statements)
1
19
0
Order By: Relevance
“…Hollander et al oberserved similar cell morphology of human primary osteoblast like cells from the iliac crest on TiAl6V4 discs processed by SLM. The vitality was comparable to flat TiAl6V4 discs, but cell density on SLM surfaces was clearly increased [25]. We also found high rates of life cells on SLM-NiTi surfaces comparable to flat glass or NiTi and an enhanced dimensional growth.…”
Section: Discussionsupporting
confidence: 54%
“…Hollander et al oberserved similar cell morphology of human primary osteoblast like cells from the iliac crest on TiAl6V4 discs processed by SLM. The vitality was comparable to flat TiAl6V4 discs, but cell density on SLM surfaces was clearly increased [25]. We also found high rates of life cells on SLM-NiTi surfaces comparable to flat glass or NiTi and an enhanced dimensional growth.…”
Section: Discussionsupporting
confidence: 54%
“…Materials Science and Engineering C 33 (2013) 419-426 By building up material by adding layers instead of removing material, they offer a nearly unlimited flexibility of the part's geometry and complexity. AM, therefore, has a high potential for the production of scaffolds, individual bone substitutes and implants [9,10]. While NiTi-SMA are gaining interest for both engineering applications and for medical applications, AM of NiTi has received less attention so far.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the production of single parts, e.g., individual implants, is challenging. In recent years, additive manufacturing (AM) has established promising methods for medical applications [9,10]. These laser assisted freeform fabrication methods provide special opportunities due to their use of the additive operation principle.…”
Section: Introductionmentioning
confidence: 99%
“…Three reviews were produced during this time that identified this technique as a viable method for production of scaffolds, as well as of prostheses and tissue models [29][30][31]. In 2003, Hollander et al [32] performed preliminary studies using XCT with SLM for the purpose of directly replacing bone using TiAl6V4 implants. The authors observed that SLM implants showed increased biocompatibility in the form of greater metabolic activity of osteoblasts when compared to non-SLM control implants, which the authors attributed to the increased surface area of SLM implants.…”
Section: History 1995-2005mentioning
confidence: 99%